E0020 Compound heterozygous novel splicing mutation D202sp and missence mutation G272D on KCNQ1 caused Jervel and Lange-Nielsen syndrome in a Chinese family. (17th November 2010) - Cuilan, Li; Wenling, Liu; Ruijuan, Liang; Xiaoliang, Qiu; Rui, Liu; Lei, Li; Jianfeng, Li; Jun, Wang; Dayi, Hu
Abstract : Background: Long QT syndrome (LQTS) is an inherited cardiac disorder characterised by QT interval prolongation on ECG, ventricular arrhythmias and sudden death. Two forms have been identified: autosomal dominant Romamo-Ward syndrome (RWS) without deafness and autosomal recessive Jervell and Lange-Nielsen syndrome (JLNS) with deafness. Methods: A Chinese family with JLNS was identified. Family members were diagnosed based on the presence of a QT interval prolongation on 12-lead ECG and a history of syncope, palpatation and deafness. Mutational screening in the KCNQ1 potassium channel gene was performed by direct DNA sequence analysis and Blast with Results: A female 12-y-o proband and her 6-y-o brother were diagnosed with JLNS in May of 2009. The QTc were 0.59 s and 0.60 s for the girl and boy, respectively. Both patients had their first syncope at the age of 2. The QTc for parents was normal. The mutation detection showed two mutations: one is a novel splicing mutation, a A to G change in the position of two bases before exon 3 (A 605-2 A→G), in the acceptor site of intron 2, which is always A followed by G. Another one is a G to A change at position of 815, which is a known missense mutation G272D reported before in a RWS European patient. Both JLNS patients were compound heterozygous for these two mutations D202sp and G272D. The father carries a heterozygous D202sp only, while the mother carries a heterozygous G272D. These two mutation were absent in 100 control alleles. The parents' marriage was not consanguineous. Because of the early age of first syncope and the less effectiveness of b-blocker for JLNS, video-assisted thoracoscopic left cardiac sympathetic denervation (LCSD) was performed successfully in June of 2009. Both patients were syncope free during 1-year follow-up after surgery at the dosage of 2.2 and 1.6 mg/Kg of proparanolol for the girl and boy. Conclusion: Our results suggest that the compound heterozygous mutation D202sp and G272D caused JLNS in the siblings of this Chinese family. To our best knowledge, this is the first report of compound heterozygous splicing and missense mutation to induce JLNS so far. The results expand the spectrum of KCNQ1 mutations causing RWS and JLNS. Further mechanism exploration will deep our understanding of this rare disease.